Viscosity and thermal properties of slag in the process of autogenous smelting of copper–zinc concentrates. (June 2015) - Selivanov, E.; Gulyaeva, R.; Istomin, S.; Belyaev, V.; Tyushnyakov, S.; Bykov, A.
<x content-type="archive" xml:space="preserve">Abstract</x> The temperature dependences of slag viscosity in the process of autogenous smelting of copper–zinc concentrated products in Vanyukov furnaces (VF) at the Sredneuralsky Copper Smeltery JSC have been revealed. Values of viscous flow activation energy have been determined. Phase transition temperatures in the processes of slag heating and cooling have been measured. The influence of calcium oxide additives on viscosity and on the crystallised slag liquidus point has been evaluated. The results obtained may be used for slag composition improvement with the purpose to reduce copper losses and simplify material preparation to subsequent depletion operation.